An Insight Of The Policy And Access To Orphan Drugs For Treating Rare Disease In Malaysia: Quantitative And Qualitative Analysis - Supian, Azuwana (2022)
An orphan drug is a medicine used to treat rare diseases. The disease has a very low population, with most of the diseases will impair the patients’ body functions and be life threatening. This study aimed to evaluate the rare disease policy and access to orphan drugs in Malaysia. Three phases have been completed. Phase one consisted of literature reviews to examine the current status of rare disease management in Malaysia and five other focus countries (Philippines, Singapore, Indonesia, Vietnam, and Thailand). They were examined based on the World Health Organisation’s (WHO) framework for action in strengthening health systems. A cross-sectional survey from ten public hospitals was also included in this phase to estimate the number of cases and treatment coverage for rare diseases in Malaysia. The second phase was designed by conducting 43 qualitative interviews and a focus group discussion on describing the perceptions among health stakeholders towards rare disease management.